Trade and Human Development - Programme des Nations Unies pour le Développement (United Nations, 2011)
Nearly four billion people live on 2 a day or less. More than a billion of them live in extreme poverty, subsisting on less than 1.25 a day. Since 2003, world trade expanded at an average annual rate of 16 per cent, before collapsing as a result of the global economic crisis in 2009. Despite the growth, the benefits of trade are still unequally distributed both within and across countries. For example in 2009, three countries accounted for 40 per cent of world merchandise exports while the 48 least developed countries accounted for less than one per cent. This publication discusses the dynamics of trade mainstreaming in developing countries by drawing on the experience of 14 case studies. The objective is to look more closely at the context in which trade mainstreaming occurs, and to identify the common elements of success in mainstreaming trade in national development strategies.